ANALYSIS OF ADHERENCE TO TAKING ANTI-TUBERCULOSIS DRUGS IN PATIENTS WITH PULMONARY TBC - Ardika Pratiwi; Akhmad Dwi Priyatno; Chairil Zaman; Nurul Fitriah; Andri Irawan (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The large number of Tuberculosis cases in the world and Indonesia's number 2, Puskesmas Gasing Laut contributes a large number of patients. There is a risk of increasing the number of Tuberculosis patients if not handled properly. This study was conducted in May-June 2025. The population and samples of this study were patients with pulmonary tuberculosis who were still undergoing treatment at the Gasing Laut Health Center. This research is quantitative with analytic survey method with cross sectional approach. Data analysis used Chi square test with a meaning level of 95% and multivariate analysis using multiple logistic regression test. The results of this study obtained a pvalue on the age variable p value 0.637, gender variable p value 0.217, education variable 0.441, knowledge 0.001, occupation 1,000, attitude 0.035, family support 0.080, side effects of drugs pvalue 0.010, distance from home to health center 1,000. So it can be concluded that there is a correlation between the variables of knowledge, attitude, family support and side effects of drugs with adherence to taking anti-tuberculosis drugs and conversely there is no correlation between the variables of age, gender, education, occupation and distance from home to the health center while the most dominant variable is knowledge with an OR value = 30.332 (95% CI: 2.408-382.129) so that respondents with high knowledge have a 30.332 times higher chance of adherence to taking Anti-Tuberculosis Drugs (OAT) than respondents with low knowledge.